1980
DOI: 10.1111/j.1467-8624.1980.tb02564.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Interaction: Consequences for Social and Mental Development at Three Years

Abstract: Interaction during feeding sessions between preterm infants and their mothers and that between full-term infants and their mothers were compared. (Mothers and babies were from a low-income, inner-city population.) When the children were about 3 years old, they attended a day camp for 3 weeks, during which their cognitive ability (Stanford-Binet) and social ability (both social competence and social participation) were assessed. Early interaction was quite different for preterms and full-terms, but in general i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
4

Year Published

1983
1983
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 17 publications
7
93
1
4
Order By: Relevance
“…At this age, beyond postpartum depression, mothers of late-preterms may experience greater symptomatology related to ongoing concern about their infant’s fragility, growth, and achievement of age-appropriate developmental milestones (Miles et al, 1999; Teti et al, 2005). In addition, mothers may be feeling overwhelmed or down as they experience asynchronous interactions with their late-preterm infant, some of which may result in infant over-arousal and negativity (Bakeman & Brown, 1980; Crnic et al, 1983; Poehlman & Fiese, 2001; Muller-Nix et al, 2004). It is also noteworthy that in the current sample nearly three times as many mothers of a late-preterm infant experienced chronically elevated depression and anxiety symptoms across the first 6 months compared to mothers of a term infant.…”
Section: Discussionmentioning
confidence: 99%
“…At this age, beyond postpartum depression, mothers of late-preterms may experience greater symptomatology related to ongoing concern about their infant’s fragility, growth, and achievement of age-appropriate developmental milestones (Miles et al, 1999; Teti et al, 2005). In addition, mothers may be feeling overwhelmed or down as they experience asynchronous interactions with their late-preterm infant, some of which may result in infant over-arousal and negativity (Bakeman & Brown, 1980; Crnic et al, 1983; Poehlman & Fiese, 2001; Muller-Nix et al, 2004). It is also noteworthy that in the current sample nearly three times as many mothers of a late-preterm infant experienced chronically elevated depression and anxiety symptoms across the first 6 months compared to mothers of a term infant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these two types of interactions relate to children’s later social and cognitive development (e.g., Bakeman, Adamson, Brown, & Eldridge, 1989; Bornstein, 1989; Clarke-Stewart, 1973; Olson, Bates, & Bayles, 1984; Smith, Adamson, & Bakeman, 1988; Yarrow, Rubenstein, & Pedersen, 1975). Bakeman and Brown (1980) found that infants who showed greater responsiveness when interacting with their mothers also interacted more with other people and did so more competently at 3 years. Olson et al (1984) found that mother–infant object-centered interactions predicted child cognitive and language competence (Bayley Mental Development Index and Peabody Picture Vocabulary Test) at 2 years, and Bornstein (1985) also found that mothers’ object-centered activities with young infants predicted children’s language and cognitive competence (vocabulary, Wechsler Preschool and Primary Scale of Intelligence) at 1 and 4 years.…”
Section: Developmental Significance Of Person-and Object-directed Intmentioning
confidence: 93%
“…This system incorporates ratings of parent and child behaviors that reflect more enduring dispositions or interactive styles (Bakeman & Brown, 1980). Considerable support exists regarding the predictive validity of these ratings for subsequent child cognitive and social development (Landry et al, 2001, 1997; Landry, Miller-Loncar, Smith, & Swank, 2002).…”
Section: Methodsmentioning
confidence: 99%